2006
DOI: 10.1111/j.1745-9125.2006.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Daylight and Darkness Targeting Strategies and the Risks of Being Seen at Residential Burglaries*

Abstract: In daylight, burglars minimized the risks of being spotted by selecting “up‐market” targets with better front cover and low occupancy that reflected the occupants' higher employment levels. After dark, townhouses with less cover were popular despite victims, fewer of whom were employed, raising more alerts. Evidence indicates consistency with routine activity theory, and target strategies appear rational, though shaped by differences in risks and offenders. Lifestyles and routine activities of victims, coupled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(119 citation statements)
references
References 23 publications
4
114
0
1
Order By: Relevance
“…Table 1 summarizes the key characteristics and findings of [7] found that increased levels of guardianship are related to significantly lower levels of crime. Coupe and Blake [8] found that guardianship operated conditionally on whether it was daylight or dark outside (though their study was not designed to examine the relationship between guardianship levels and crime specifically). Lynch and Cantor [28] found that guardianship at the block level has a significant effect on burglary risk.…”
Section: Effect Of Guardianship On Crimementioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes the key characteristics and findings of [7] found that increased levels of guardianship are related to significantly lower levels of crime. Coupe and Blake [8] found that guardianship operated conditionally on whether it was daylight or dark outside (though their study was not designed to examine the relationship between guardianship levels and crime specifically). Lynch and Cantor [28] found that guardianship at the block level has a significant effect on burglary risk.…”
Section: Effect Of Guardianship On Crimementioning
confidence: 99%
“…Coupe and Blake [8] measured guardianship through the use of security devices, whether or not the burglar was spotted, and whether the household was occupied at the time of the burglary. The concern with this study is that it only used reported cases of burglary and there were no households included that did not experience burglaries to examine the influence of guardianship on crime outcomes.…”
Section: Measuring Guardianshipmentioning
confidence: 99%
“…Studies analyzing the offender decision-making process related to the location of the crime have mostly been carried out for property crimes such as burglary (e.g., Bernasco & Nieuwbeerta, 2005;Clare, Fernandez, & Morgan, 2009;Coupe & Blake, 2006;Nee & Meenaghan, 2006;Wright, Logie, & Decker, 1995) and robbery (e.g., Bernasco & Block, 2009;Bernasco, Block, & Ruiter, 2013;Petrosino & Brensilber, 2003). Recent studies have also investigated target selection and spatial choices of rioters (e.g., Baudains et al, 2013;Martin, McCarthy, & McPhail, 2009).…”
Section: Environmental Consistency and Serial Offendersmentioning
confidence: 99%
“…We investigate the effectiveness of gatingon burglary both during the day and during the night since previous research has shown how burglars change their targeting strategies depending on whether it is day time or night time (see Coupe and Blake, 2006). Employing methods of analytical research, we determine whether the extent of burglary in gated communities is higher or lower than in the immediate surrounding areas, as well as compare the extent of burglary in gated communities with burglary across an entire city.…”
Section: Introductionmentioning
confidence: 99%